PENYELESAIANNYA PEMBAGIAN WARISAN TANPA MELALUI PENGADILAN MELALUI METODE TASHALUH - Abduh, Muhammad (Program Studi Hukum Keluarga Islam, 2022)
This research highlights the importance of resolving inheritance disputes in Indonesia through the Tashaluh method, an amicable approach that integrates the principles of sharia, adat and local traditions. The general background shows that inheritance conflicts often impose significant financial and emotional burdens and can disrupt family relationships. On the other hand, the specific background highlights the need for alternative methods such as Tashaluh in addressing the different interpretations of inheritance laws from customary, religious and national laws that are often the starting point of conflict. This research fills the knowledge gap by exploring the potential of the Tashaluh method in defusing inheritance conflicts and maintaining family harmony. Through a normative-empirical approach, this research uses deductive and inductive approaches to analyze the phenomenon of inheritance division in society. The main findings show that the Tashaluh method can be an effective alternative in resolving inheritance disputes by maintaining cultural and religious sustainability and enriching traditional means of conflict resolution. The implications of this research provide new insights for Islamic law practitioners and researchers in strengthening the legitimacy of resolving inheritance disputes in accordance with the cultural and social context of the community, as well as highlighting the importance of further research to explore the long-term impact of using the Tashaluh method on social stability, economy, and justice in the community.